Diversity and Abundance of Wetland Birds around Kurukshetra, India - Kumar, P.; Gupta, S.K. (Our Nature, 2010)
Kurukshrtra is a place of great historical and religious importance in India and is dotted with a number of holy water bodies and ponds. These wetlands support a rich avian diversity and serve as winter sojourn. A total of 54 species of wetland birds belonging to 36 genera and 15 families distributed in 5 orders have been recorded around Kurukshrtra .These wetlands are under pressure from diverse anthropogenic activities. This paper provides an overview of status of wetland birds and threats to them in the study area. Key words: Wetland birds, diversity, abundance, Kurukshetra DOI: 10.3126/on.v7i1.2574 Our Nature (2009) 7:212-217